ECONOMICS STUDENTS’ PERCEPTION, ATITUDE AND MOTIVATION TOWARD LEARNING ENGLISH LANGUAGE - Rahmania .; Anni Holila Pulungan; I Wayan Dirgeyasa (Universitas Negeri Medan, 2020)
This study aimed (1) to describe the perception, attitude and motivation of Economics students in learning English. (2) to describe level of perception, the level of attitude and level of motivation of Economics students in learning English.(3) to reason why the Economics students realize such perception, attitude and motivation in learning English as the ways they are. This qualitative study was conducted at the first year of Economics students. The sources of data of this study were 58 students from two classes. The data were collected by share questionnaire and interviews then were analyzed using Interactive Models. The result showed that (1) the students perceive the important of English for his/her study and future work and students offer the general abstract statement of the important of English. They have positive attitude and negative attitudes and integrative instrumental, intrinsic and extrinsic motivation; (2) level of perception of Economics students were 485 highly positive, 33% positive and 19 % negative, then the level of attitude in the level of receiving (78%), valuing (64%), internalizing values (63%), responding (50%) and organizing (43%). The level of motivation was high. (3)some reason of students realized their perception were work, study, promote economy syariah language policy and lack of skill. For reason of students realized their attitudes were economical factor, ethnicity, language policy, occupation and listen the music, three reasons of students realized their motivation were the physical condition of class, lecturer and method of teaching.Keywords: English, Learning, Perception, Attitude, Motivation.